Analysis of E-Commerce Usage on Consumer Behavior from an Islamic Perspective: Case Study of Sharia Economics Students at Mulawarman University - Rahmi Ramadani; Rabiatul Adawiyah (FEB Universitas Mulawarman, 2025)
The development of digital technology has driven the increased use of e-commerce among university students, including those who are Muslim. This phenomenon has the potential to influence consumption patterns that should be based on Islamic values. This study aims to analyze the consumption behavior of Muslim students in using e-commerce from an Islamic perspective, with a focus on the application of the principles of halal (permissible), simplicity, tawhid (monotheism), and trustworthiness (amanah). This study used a descriptive qualitative approach with in-depth interviews with five students of the Sharia Economics Study Program at Mulawarman University who actively shop through e-commerce. The data obtained were analyzed using thematic analysis to identify consumption behavior patterns that align with Islamic principles. The results show that e-commerce simplifies and increases the efficiency of students' shopping activities, but also has the potential to trigger consumptive behavior. Overall, informants strive to apply halal principles by selecting products with clear halal certification, maintaining simplicity, and upholding the values of tawhid (monotheism) and trustworthiness in every transaction. Thus, the use of e-commerce can be in line with Islamic teachings if supported by spiritual awareness and moral responsibility